”I feel unappreciated because I’m not the real teacher”: Understanding pre-service teachers’ emotions and identity - Murtiana, Rahmila; Risdaneva, Risdaneva (English Education Department, Universitas Islam Indonesia, 2025)
This study explores the emotional experiences of pre-service teachers (PSTs) during their teaching practicum and examines how these emotions shape their emerging teacher identities. This narrative study explores the personal stories of five PSTs, each reflecting unique challenges and emotional responses. The data were gathered through in-depth interviews with each participant, analysed using narrative analysis, and presented as reconstructed stories. The findings reveal that PSTs frequently experience negative emotions such as frustration, anxiety, anger, and a sense of being unappreciated. These emotions arise from student behaviour and the challenges associated with classroom management. Positive emotions such as satisfaction and pride also emerge. However, the struggles with self-doubt and feelings of being undervalued were more prevalent. These narratives highlight the crucial role of understanding PSTs’ emotions as they navigate into the complexities of teaching practicum. The findings of the study underscore the need for emotional support, collaboration, and guidance to foster resilience and confidence among PSTs, ultimately shaping their sense of teacher identity in positive ways.